PULAU SEBATIK: KAWASAN PERBATASAN INDONESIA BERAROMA MALAYSIA - Siburian, Robert (Jurnal Masyarakat dan Budaya, 2015)
This article is based on a field research conducted in September 2011. The island of Sebatik belongs to two countries: Indonesia and Malaysia. The southern part of Sebatik is owned Indonesia and the northern is owned by Malaysia. Sebatik island is located between Nunukan, the capital of Nunukan District in Indonesia and Tawau, the capital of Tawau District in Malaysia. Indonesia's Sebatik is not a business center but its population is growing rapidly. Most of the inhabitants are migrants who came from many places in Indonesia, mainly from South Sulawesi. As a place that is very close to Tawau, a business center in Sarawak, Malaysia, the dynamic of Indonesian Sebatik economy is very dependent on economic conditions in Tawau. Many goods that are consumed by Indonesian Sebatik inhabitants, such as canned food and and drinks, electronic goods, and gas are imported from Tawau, The products come into Sebatik under border trade agreement through an MOU signed by Indonesian and Malaysian governments in 1967. In addition, the use of the Malaysia ringgit currency as a means of transactions has made the economy in Indonesian Sebatik smelt Malaysia. This article seeks to explore the dynamics of economic conditions in Sebatik as a border area, its economic potentials, the use of dual money currency, and finally what will happen to Sebatik's economy without Tawau.